Composição corporal e exigências de energia e proteína para borregas Santa Inês gestantes - Fernando Antônio de Souza (2013)
This study aimed to determine the net energy and protein requirements for nulliparous Santa Ines ewes, pregnant at different gestational ages. For this, 27 ewes aged approximately 12 months, pregnant were fed to two nutritional levels during three different stages of gestation (100,130 and 140 days of gestation) in a completely randomized experimental design with a 4x2 factorial arrangement (stage physiological vs. nutritional level ) . The nutricional levels were applied through the formulation of two different diets which varied in their forage: concentrate ratio. Diets were formulated to meet the needs of 100% of energy and protein of the animal (High Level Group) and 85% of these needs (low group). Eleven animals non-pregnant were randomly assigned togroups of nutritional levels by an average of 55 days and then slaughtered to serve as the reference group for the comparative slaughter method. The pregnant animals were slaughtered according to gestational age and his body was evaluated for content of protein, fat and energy. The requirement for energy and protein was obtained according to the methodology proposed by ARC (1980). An independent trial was realized to estimate the heat production by the respirometric method with nulliparous ewes pregnant single, to 100 and 130 days gestational age fed the same nutritional level used for the comparative slaughter method with the objective of comparing the values obtained by both methods. The results showed effect of the nutritional levels and gestational age on body composition and the maternal body tissue mobilization on nutritional levels evaluated were able to maintain the development of gravid uterus and no effect of nutritional level on gravid uterus was observed. The net energy requirement for maintenance and gain estimated in this study was 66.89 kcal/EBW0.75 (EBW, Empty Body Weight) and 4.5 to 5.4 Mcal / kg EBW0.75 respectively. The protein requirement for maintenance and gain estimated was 3.04 grams / day and 276-273 grams / kg EBW0.75. The net energy requirement and protein for the development of the gravid uterus was dependent on the gestational age and ranged from 61-116 Kcal and 5.8 to 15.5 g / day respectively. The net energy requirement forprotein and mammary gland development was dependent on the nutritional level and two regression models was necessary to estimate your requirement which ranged from 22 to 95 kcal / day, and 1.6 to 8.7 grams / days respectively. A comparison of net energy requirement obtained by the comparative method of killing was compared to the heatproduction and estimated by the respirometric method was not observed differences between the values obtained by these methods.